ANALYSIS OF FACTORS AFFECTING THE COMPOSITE STOCK PRICE INDEX OF CONSUMPTION GOODS IN THE INDONESIA STOCK EXCHANGE - Salwan Hanafi; Sri Indah Nikensari; Saparuddin Mukhtar (Yayasan Education and Social Center, 2022)
Uncertainty in the world economy has and will continue to overshadow any composite stock price index anywhere. This study aims to examine the effect of domestic inflation, the Fed interest rate and the volume of stock transactions on the composite stock price index of the Consumer Goods Sector in Indonesia for the period January 2018-April 2021, a period before the Russia- Ukraine war. Multiple linear regression equations were used to analyze the data, sourced from Bank Indonesia, the Indonesia Stock Exchange, and The Federal Reserve. The results showed that all proposed variables had a significant effect on the composite stock price index of the consumer goods sector. These results provide an indication that the inflation rate in a country and the interest rate policy of the United States Central Bank, its can affect a country composite stock price index, while the volume of consumer goods stock transactions also affects its stock price index